CERULOPLASMIN PLASMA LEVELS IN PATIENTS WITH SEVERE FORMS OF HERPES INFECTION - Novikova, Irina; Zlotnikova, Maria (Biomedical papers, 2011)
Background: Research interest in ceruloplasmin (CP) has significantly increased in recent years owing to new discoveries of its properties including anti-inflammatory and anti-oxidant effects. Data on CP blood plasma level in patients with herpetic infection caused by herpes simplex virus are scarce and often contradictory. Most point to a reduction of CP in the blood plasma of patients during the exacerbation of the disease with gradually return to normal values after treatment. There is evidence of an increase in CP levels during the acute period of CRHI (chronic recurrent herpes infection) and decrease in remission.Materials and methods: The content of ceruloplasmin in blood plasma was determined by immunoturbidimetry using the test-systems ``Spinreact'' (Spain) and biochemical analyzer ``Architect C8000''.Results: We found that in patients with severe forms of chronic recurrent herpes infection in the exacerbation period, CP levels were increased by approximately 35% relative to the control values. However in the remission period in 80% of patients, CP concentrations remained elevated and in some patients the CP level was even increased in comparison with values in the exacerbation. Such dynamics of CP were not caused by the exacerbation of concomitant diseases.Conclusion: The increased CP levels in the remission period in patients with severe forms of chronic recurrent herpes infection may have been caused by its effect as an endogenous antioxidant. No correlations of CP levels with other laboratory signs of acute inflammation were found but identified was a relation to free radical activity.
Keywords: Herpes infection/Ceruloplasmin/C-reactive protein